Peer Assessment of Oral Presentations in EFL Classes: Assessors’ View - Daukšaitė-Kolpakovienė, Aurelija; Mačianskienė, Nemira (Pedagogika, 2023)
The study focuses on peer assessment (PA) used in teaching English as a foreign language. It aimed to identify students’ attitudes towards PA in oral presentations, using online PA forms and an online post PA questionnaire. Thematic analysis of the data show positive students’ attitudes towards PA, as it helped them to understand the task requirements better, be more focused, and improve their own presentation skills. The drawbacks were linked to stress during the assessment.